Brain Activations During Optokinetic Stimulation in Acute Right-Hemisphere Stroke Patients and Hemispatial Neglect: An fMRI Study. (July 2019) - von der Gablentz, Janina; Könemund, Inga; Sprenger, Andreas; Heide, Wolfgang; Heldmann, Marcus; Helmchen, Christoph; Machner, Björn
Objective . Leftward optokinetic stimulation (OKS) is a promising therapeutic approach for right-hemisphere stroke patients with left hemispatial neglect. We questioned whether the putative neural basis is an activation of frontoparietal brain regions involved in the control of eye movements and spatial attention. Methods . We used functional magnetic resonance imaging to investigate brain activations during OKS in acute right-hemisphere stroke patients (RHS, n = 19) compared with healthy control subjects (HC, n = 9). Based on neuropsychological testing we determined the ipsilesional attention bias in all RHS patients, 11 showed manifest hemispatial neglect. Results . In HC subjects, OKS in either direction led to bilateral activation of the visual cortex (V1-V4), frontal (FEF) and supplementary (SEF) eye fields, intraparietal sulcus (IPS), basal ganglia, and thalamus. RHS patients' activations were generally reduced compared with HC. Nevertheless, leftward OKS bilaterally activated the visual cortex (V1-V4), FEF, SEF, IPS, and thalamus. The neural response to OKS was negatively correlated with patients' behavioral impairment: The greater the individual attention bias/neglect the weaker the brain activations. Conclusion . In RHS patients, leftward OKS activates frontoparietal regions (FEF, IPS) that are spared from structural brain damage and functionally involved in both oculomotor control and spatial attention. This may provide a neural basis for the known therapeutic effects of OKS on hemispatial neglect. In acute stroke stages, reduced activation levels correlating with neglect severity indicate functional downregulation of the underlying dorsal attention network. Therefore, chronic RHS patients with less severe neglect after recovery of network disturbances may be more suitable candidates for OKS rehabilitation.